Source data for “The effects of water column dissolved oxygen concentrations on lake methane emissions: Results from a whole-lake oxygenation experiment” - Pajala, Gustav (Linköping University, 2022)
Data behind the article "The Effects of Water Column Dissolved Oxygen Concentrations on Lake Methane Emissions—Results From a Whole-Lake Oxygenation Experiment" by Gustav Pajala et al.

In this study we measured CH4 emissions from two connected lake basins, one where we increased concentrations of dissolved oxygen in the water column (Experimental basin), and one that was left in a natural state, resulting in deep water oxygen depletion (Reference basin). In the Experimental basin, the dissolved oxygen addition resulted in negligible CH4 accumulation in the water column. In the Reference basin, CH4 accumulated in anoxic water layers. However, no clear difference in CH4 emissions among the two basins could be detected during the summer. The basins only partially mixed in fall and spring and depending on the degree and intensity of water column mixing, we estimated that 0%–24% of CH4 stored in the water column was released upon fall and spring turnover, while the rest was converted to carbon dioxide by methane-oxidizing bacteria. Accordingly, water column anoxia may not be important for CH4 emissions from all boreal lakes but can represent a main share of the yearly CH4 emissions in some lakes.

The dataset was originally published in DiVA and moved to SND in 2024.
Source data for “The effects of water column dissolved oxygen concentrations on lake methane emissions: Results from a whole-lake oxygenation experiment”
Keywords: lakes; sjöar; oxygen; syre; methane; metan; Environmental Sciences; Miljövetenskap